Length-weight relationship of Asian seabass, Lates calcarifer (Bloch) reared in open sea floating cages - Philipose, K. K.; Damodaran, Divu; Krupesha Sharma, S. R.; Vaidya, N. G.; Sadhu, N.; N. Dube, Praveen (Indian Journal of Fisheries, 2013)
The paper presents the length-weight relationship (LWR) parameters of Lates calcarifer reared in open sea floating cages off Karwar along the south-west coast of India. The relationship obtained in the present study was W = 0.000008299L3.088 which indicates that seabass reared in open sea floating cages in semi-intensive condition does not differ significantly in body appearance from their counterparts found in natural conditions. The growth of the fishes was found to be positively allometric.